ASSESSMENT OF SOCIAL PROBLEM OCCURANCE AMONG YOUTH IN KELANTAN THROUGH THE INTEGRATION OF GIS ANALYSIS - Nur Azah Izaty Abd Aziz; Nazirah Md Tarmizi; Noorazwani Mohd Razi; Nursyahani Nasron; Noor Azura Zainudin, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Religious life that is also known as piety, is the highest level of a Muslim. It could be achieved through the practicing and appreciating of high religion based on true understanding. However, in recent years, there have been many criminal cases and social problems reported happening among young people and religious people, especially in Kelantan. This study was conducted with the aim to perceive the relationship between the appreciation of Islamic studies among the youth of Kelantan and the occurrence of social problems by using geospatial analysis. On the other hand, it was known that the basis of learning and mastery of the Islamic religion begins with studying the Quran. The important is it could serve as a guide for every Muslim. However, the level of appreciation can also be influenced by the physical environment. This study involved 250 random respondents covering all districts in Kelantan. A set of questionnaires have been prepared and distributed to the youths through social media such as WhatsApp and Telegram. For the crime cases analysis, the studies used police report data for the purpose of detecting hotspots of crime in the study area. Results of the study show a positive relationship between the appreciation of Islamic studies and social problems among youth in Kelantan and the distribution of incidents was shown in terms of spatial interpolation using Inverse Distance Weightage (IDW).